Effects of Steady Low-Intensity Exercise on High-Fat Diet Stimulated Breast Cancer Progression Via the Alteration of Macrophage Polarization. (September 2020) - Kim, Min Kyoon; Kim, Yesl; Park, SeungHwa; Kim, Eunju; Kim, Yerin; Kim, Yuri; Kim, Jung-Hyun
Physical inactivity and high-fat diet, especially high saturated fat containing diet are established risk factors for breast cancer that are amenable to intervention. High-fat diet has been shown to induce tumor growth and metastasis by alteration of inflammation but steady exercise has anti-tumorigenic effects. However, the mechanisms underlying the effects of physical activity on high-fat diet stimulated breast cancer initiation and progression are currently unclear. In this study, we examined how the intensity of physical activity influences high fat diet-stimulated breast cancer latency and progression outcomes, and the possible mechanisms behind these effects. Five-week-old female Balb/c mice were fed either a control diet or a high-fat diet for 8 weeks, and then 4T1 mouse mammary tumor cells were inoculated into the mammary fat pads. Exercise training occurred before tumor cell injection, and tumor latency and tumor volume were measured. Mice with a high-fat diet and low-intensity exercise (HFLE) had a longer tumor latency period, slower tumor growth, and smaller tumor volume in the final tumor assessment compared with the control, high-fat diet control (HFDC), and high-fat diet with moderate-intensity exercise (HFME) groups. Steady low- and moderate-intensity exercise had no effect on cell proliferation but induced apoptosis by activating caspase-3 through the alteration of Bcl-2, Bcl-xL, and Bax expression. Furthermore, steady exercise reduced M2 macrophage polarization in breast tumor tissue, which has been linked to tumor growth. The myokine, myostatin, reduced M2 macrophage polarization through the inhibition of the JAK-STAT signaling pathway. These results suggest that steady low-intensity exercise could delay breast cancer initiation and growth and reduce tumor volume through the induction of tumor cell apoptosis and the suppression of M2 macrophage polarization.